Bipolar Organic Material Assisted Surface and Boundary Defects Passivation for Highly Efficient MAPbI3‐Based Inverted Perovskite Solar Cells. Issue 11 (22nd September 2020) - Syed, Ali Asgher; Miao, Yawei; Sathiyan, Govindasamy; Chen, Cheng; Zheng, Mengmeng; Yang, Xichuan; Ji, Hongbing; Li, Huaming; Cheng, Ming
Abstract : At the device operating conditions, defects such as interstitials, vacancies, and impurities at the grain boundary and surface of photoactive layer have great impact on the power conversion efficiency (PCE) and device stability. To better passivate the surface and boundary defects, and further enhance the PCE and device stability, herein, a bipolar organic material termed 1, 4‐bis(perfluorophenyl)‐2, 5‐di(pyridin‐4‐yl)‐1, 4‐dihydropyrrolo [3, 2‐ b ] pyrrole (PFPPY) is introduced as modifier in antisolvent. The effects of PFPPY on perovskite film quality, photovoltaic performance, and charge transfer properties are systematically investigated. Under the optimized conditions, the PFPPY‐treated device shows an impressive PCE of 19.62%, which is 12% higher than the reference device (17.59%), and greatly enhanced stability, maintaining 95% of its initial efficiency under room temperature (RT) and relative humidity (RH) 30% condition for 650 h without encapsulation. Abstract : A bipolar organic material 1, 4‐bis(perfluorophenyl)‐2, 5‐di(pyridin‐4‐yl)‐1, 4‐dihydropyrrolo [3, 2‐ b ] pyrrole (PFPPY) is utilized to passivate perovskite surface and boundary defects via solvent engineering approach, generating an impressive power conversion efficiency (PCE) of 19.62% and greatly enhanced stability.